Mutant SPART causes defects in mitochondrial protein import and bioenergetics reversed by Coenzyme Q - Chiara Diquigiovanni; Nicola Rizzardi; Antje Kampmeier; Irene Liparulo; Francesca Bianco; Bianca De Nicolo; Erica Cataldi-Stagetti; Elisabetta Cuna; Giulia Severi; Marco Seri; Miriam Bertrand; Tobias B. Haack; et al. (Open Biology, 2023)
Pathogenic variants in SPART cause Troyer syndrome, characterized by lower extremity spasticity and weakness, short stature and cognitive impairment, and a severe mitochondrial impairment. Herein, we report the identification of a role of Spartin in nuclear-encoded mitochondrial proteins. SPART biallelic missense variants were detected in a 5-year-old boy with short stature, developmental delay and muscle weakness with impaired walking distance. Patient-derived fibroblasts showed an altered mitochondrial network, decreased mitochondrial respiration, increased mitochondrial reactive oxygen species and altered Ca2+ versus control cells. We investigated the mitochondrial import of nuclear-encoded proteins in these fibroblasts and in another cell model carrying a SPART loss-of-function mutation. In both cell models the mitochondrial import was impaired, leading to a significant decrease in different proteins, including two key enzymes involved in CoQ10 (CoQ) synthesis, COQ7 and COQ9, with a severe reduction in CoQ content, versus control cells. CoQ supplementation restored cellular ATP levels to the same extent shown by the re-expression of wild-type SPART, suggesting CoQ treatment as a promising therapeutic approach for patients carrying mutations in SPART.